2024
DOI: 10.1111/bph.16294
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1‐mediated regulation of smooth muscle cell volume in response to enhanced extracellular matrix rigidity

Robert T. Johnson,
Reesha Solanki,
Finn Wostear
et al.

Abstract: Background and PurposeDecreased aortic compliance is a precursor to numerous cardiovascular diseases. Compliance is regulated by the rigidity of the aortic wall and the vascular smooth muscle cells (VSMCs). Extracellular matrix stiffening, observed during ageing, reduces compliance. In response to increased rigidity, VSMCs generate enhanced contractile forces that result in VSMC stiffening and a further reduction in compliance. Mechanisms driving VSMC response to matrix rigidity remain poorly defined.Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…VSMCs are known to possess multiple stretch-activated ion channels, and these can vary depending on phenotype. We have previously shown that piezo1 is upregulated in disease relevant phenotypes (Johnson et al, 2024). It remains unknown whether the VSMC tensegrity equilibrium can be altered in healthy contractile differentiated VSMCs, but microtubule agents alter VSMC contractile function in isolated aortic rings, suggesting that this is the case (Zhang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…VSMCs are known to possess multiple stretch-activated ion channels, and these can vary depending on phenotype. We have previously shown that piezo1 is upregulated in disease relevant phenotypes (Johnson et al, 2024). It remains unknown whether the VSMC tensegrity equilibrium can be altered in healthy contractile differentiated VSMCs, but microtubule agents alter VSMC contractile function in isolated aortic rings, suggesting that this is the case (Zhang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used Ca 2+ flux as a readout of stretch-activated channel function. One of these, piezo1, is emerging as an important regulator of VSMC dysfunction (Johnson et al, 2024; Luu et al, 2023; Qian et al, 2022; Retailleau et al, 2015; Swiatlowska et al, 2023). Our findings further implicate piezo1, as a critical regulator of VSMC behaviour and suggest that changes in piezo1 opening drive altered VSMC behaviour in response to enhanced matrix stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations